Performing law: space and the unfolding of gender and violence in India - Kokal, Kalindi; Menski, Werner (Handbook on Space, Place and Law, 2021)
Spaces of law and the scales at which they function are crucial to the implementation of laws. This chapter explores how women in urban India use concepts of gender and violence to access state law in different forums to unfurl various formal and informal processes that combine to construct a sense of justice. Simultaneously we show how state laws aimed at protecting women from gender-based violence are experienced differently in different spaces, provoking a discussion about the limits and extent of such laws. Conflicts over space, place and time arise, everywhere, simply because ‘law’ as ‘living law’ is much more than rules of state law and includes norms, religious beliefs and everyday practices and is used or performed strategically by different actors.<br